The use of poultry by- product meal as replacement of protein concentrate in broiler diets - AL-Taee, Sabah N.; AL-Kaissy, Galibe A.; Ali, Abdul-Amir (The Iraqi Journal of Veterinary Medicine, 2003)
Atotal of 720 Isa broiler one- day old chicks were used in this study. They were fed a commercial diet for the first two week of the study which last for 8 weeks. Thereafter chick were divided into 4 equal groups (a,b,c.and d). Each group contained 180 chicks in triplicates. Afloor pens were used in raring the chicks for the entire period of eight weeks. The diets a,b,and c contained a poultry by-product meal at a rate of 10% for the entire period as a source of animal protein. This local crud protein was bought as a meal from three processing plant named Abu-Ghraib, Dorrha, and Sammarha (a,b,c), respectivelly. Whereas in diet (d) a foreign protein concentrate was used as a soure of protein and left as a control. Results indicated that the final body weight of bird in group (a) and (b) was 1863 and 1606 gm respectivelly. These averages were higher (p<0.05) than that (1300gm.) reported from birds in group (d) that received the concentrate. On the other hand statistical analysis did not show any significanc difference in feed efficiency among these groups. Furthermore data from this study indicated that group (c) which received the poultry by- product from Samarrah processing plant gave the lowest (p<0.05) body weight (1056 gm.) as compaired to other groups of the experiment. Feed efficiency of birds in this group was also the lowest (3.55) among all other groups. It is concluded that poultry by- product meal can be used as a replacement to protein concentrate in broiler diets.